2012
DOI: 10.1111/j.1478-5153.2012.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Iranian intensive care nurses' experience of end‐of‐life care: a qualitative study*

Abstract: Managers ought to provide specialized units for providing care to end-of-life patients. Nurses working on these units will require emotional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
4
32
0
10
Order By: Relevance
“…Thus, their cultural, religious and ethical beliefs meant that nurses cared for patients, regardless of their illness or religion. This is consistent with the report by Valiee et al () who reported that most Iranian health care providers were Muslims who believed in life after death, and that social, cultural and religious backgrounds significantly affected their attitude towards end‐of‐life care. Most of our participants were pleased to care for any patient admitted to the hospital and used their skills to give the patients another chance to return to their daily activities and to live a normal life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, their cultural, religious and ethical beliefs meant that nurses cared for patients, regardless of their illness or religion. This is consistent with the report by Valiee et al () who reported that most Iranian health care providers were Muslims who believed in life after death, and that social, cultural and religious backgrounds significantly affected their attitude towards end‐of‐life care. Most of our participants were pleased to care for any patient admitted to the hospital and used their skills to give the patients another chance to return to their daily activities and to live a normal life.…”
Section: Discussionsupporting
confidence: 92%
“…Patients suffering from life‐threatening diseases such as cancer, heart disease, stroke and chronic respiratory diseases are admitted to the ICU of hospitals (Payne et al , ). The challenge for intensive care nurses is to provide the best possible care to patients (Valiee et al , ). Advancement in medical technology has contributed a lot to increasing patient's life span, improving the quality of the provided care (Beckstrand and Kirchhoff, ).…”
Section: Introductionmentioning
confidence: 99%
“…Providing end‐of‐life care has profound positive and negative psychosocial effects on nurses, with the latter being more prominent (King & Thomas, ). In addition, they faced ethical dilemma when they were organisationally obligated (Valiee, Negarandeh, & Dehghan Nayeri, ) to provide active treatment when they perceived it as futile when doctors or family members were unwilling to start palliative care (McCallum & McConigley, ). As such, they coped using active and passive coping techniques (Hinderer, ; Ranse et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such patients are transferred to ICUs to receive advanced care using sophisticated medical technologies, with the aim of prolonging their life expectancy (Williams et al 2003). However, even with the critical care which provides in ICU, dying of some patients is inevitable which in turn affects the nurses more than other health care team and could be attributed to the relationship that has formed during caring encounters among the nurse, patient and his or her relatives (Valiee, Negarandeh & Dehghan Nayeri 2012).…”
Section: Introductionmentioning
confidence: 99%